2006
DOI: 10.1007/s11886-006-0063-5
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet resistance with aspirin and clopidogrel: Is it real and does it matter?

Abstract: Platelets play a pivotal role in the pathophysiology of ischemic complications of atherosclerotic cardiovascular disease. Aspirin and clopidogrel are oral antiplatelet drugs that have been shown to reduce adverse clinical events across the wide spectrum of patients with atherothrombotic disease. However, recurrent ischemic events still occur in a significant proportion of patients despite treatment with these antiplatelet drugs. The concept of antiplatelet resistance therefore emerges. Although uniform definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…1); however, some have several collateral effects and resistance in long term therapy, such as the known clinical aspirin resistance 6) . In fact, numerous studies have documented inter-individual variability in platelet responsiveness to aspirin and clopidogrel, some of the most used oral antiplatelet drugs 7) . The feasibility of using antiplatelet agents to substitute oral anticoagulant treatment has also been discussed in the literature for secondary prevention of further vascular events after limited ischaemic stroke of arterial origin due to their lower risk 8) .…”
Section: Introductionmentioning
confidence: 99%
“…1); however, some have several collateral effects and resistance in long term therapy, such as the known clinical aspirin resistance 6) . In fact, numerous studies have documented inter-individual variability in platelet responsiveness to aspirin and clopidogrel, some of the most used oral antiplatelet drugs 7) . The feasibility of using antiplatelet agents to substitute oral anticoagulant treatment has also been discussed in the literature for secondary prevention of further vascular events after limited ischaemic stroke of arterial origin due to their lower risk 8) .…”
Section: Introductionmentioning
confidence: 99%
“…6 -8 Notably, some investigators have shown that posttreatment platelet reactivity is a better predictor of thrombotic risk than change in platelet aggregation from baseline to posttreatment. 9,10 Nevertheless, evidence suggests that patients taking aspirin or clopidogrel with hyporesponsiveness to antiplatelet treatment in ex vivo or in vitro assays may be at higher risk of developing ischemic events, often termed "antiplatelet resistance" 11 ; however, these studies have limitations and no clear "cutoff" for inhibitory activity and subsequent risk has been defined.…”
Section: What Is Vpr?mentioning
confidence: 99%
“…These drugs include acetylsalicylic acid, clopidogrel, eptifibatide, triflusal and tirofiban; however, some have several indemnity effects and battle in long term therapy, such as the known clinical aspirin resistance [ 3 ]. Several studies also have reported inter-individual variability in platelet reaction to aspirin and clopidogrel, the well-known oral antiplatelet drugs [ 4 ]. The possibility of using antiplatelet agents to substitute oral anticoagulant treatment has been reported in the literature for secondary prevention of further vascular events after limited ischemic stroke due to their lower risk [ 5 ].…”
Section: Introductionmentioning
confidence: 99%